2015
DOI: 10.1111/acem.12717
|View full text |Cite
|
Sign up to set email alerts
|

A Preprocedural Checklist Improves the Safety of Emergency Department Intubation of Trauma Patients

Abstract: Objectives Endotracheal intubation of trauma patients is a vital and high‐risk procedure in the emergency department (ED). The hypothesis was that implementation of a standardized, preprocedural checklist would improve the safety of this procedure. Methods A preprocedural intubation checklist was developed and then implemented in a prospective pre‐/postinterventional study in an academic trauma center ED. The proportions of trauma patients older than 16 years who experienced intubation‐related complications du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
81
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(86 citation statements)
references
References 9 publications
(10 reference statements)
3
81
0
2
Order By: Relevance
“…Using statistical process control methods, the improvements were temporally related to implementation of the "Intubation Timeout" tool [27]. The authors concluded that the improvements noted were due to improvements in team communication and function prior to, and during, the intubation encounter, a finding which has been reported in adult and pediatric intubations as well [28][29][30].…”
Section: Neonatal Intubation Safety Researchmentioning
confidence: 88%
“…Using statistical process control methods, the improvements were temporally related to implementation of the "Intubation Timeout" tool [27]. The authors concluded that the improvements noted were due to improvements in team communication and function prior to, and during, the intubation encounter, a finding which has been reported in adult and pediatric intubations as well [28][29][30].…”
Section: Neonatal Intubation Safety Researchmentioning
confidence: 88%
“…12 Arguably, novices should not perform this procedure in EDs, with stronger consideration given to the acquisition of laryngoscopy and intubation skills in the controlled setting of the operating theatre or simulation environment. 19,20 Factors associated with improved first attempt success rate included video laryngoscopy, bougie use and a CL grade I or grade II view. The majority of patients were men, and most had a medical indication for intubation, similar to other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Although a pre-intubation checklist did not favourably influence success or complication rates, we support its use due to the potential to reduce stress and error during this high-risk procedure. 19,20 Factors associated with improved first attempt success rate included video laryngoscopy, bougie use and a CL grade I or grade II view. This is consistent with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…We applaud the recent study by Smith et al . highlighting the impact that preprocedure checklists can have on safety metrics of peri‐intubation care in trauma patients.…”
mentioning
confidence: 88%